Participation in the Child and Adult Care Food Program Influences Nutrition-Related Practices of Child Care Settings in Nebraska (P04-172-19). (13th June 2019) - Williams, Bethany; Sisson, Susan; Padasas, Irene; Dev, Dipti
Abstract: Objectives: Federal food assistance programs such as the Child and Adult Care Food program (CACFP) are designed to promote healthy dietary habits for young children; the present study will aim to determine how CACFP participation influences implementation of nutrition-related best practices and barriers in childcare settings. Methods: Cross-sectional surveys were distributed to 3014 licensed childcare facilities in Nebraska in 2017 to collect provider-reported information on facility demographics, CACFP participation, and practices implemented in childcare settings serving children aged 2–5 years. Chi-square analysis was performed in SPSS to determine differences in best practice implementation, barriers, and difficulty level between those who do versus do not participate in the CACFP, stratified by childcare context (center-based versus family childcare home-based). Results: The sample included 1345 childcare programs (54.6% response rate); 86.8% participated in the CACFP, 21.7% were center-based, and 78.3% were home-based. Childcare programs who participated in the CACFP were more likely to serve foods and beverages according to best practices across both contexts; practices included serving fruit at least one time, serving vegetables at least one time, and serving skim or 1% milk ( P  < 0.05 for all). In family childcare homes only, those who participated in the CACFP were more likely to role model eating healthy foods and serve meals family style ( P  < 0.05 for both). Across both contexts, those who participated in the CACFP were more likely to receive professional development on child nutrition ( P  < 0.01). Conclusions: While participation in the CACFP was related to higher prevalence of serving healthier food and beverages, few mealtime practices were affected. This could be attributed to CACFP regulations requiring participating childcare programs to serve nutritious food and beverages to children, but only recommend mealtime-related best practices. These findings could suggest that CACFP-related trainings should emphasize the importance of these practices with consideration of known provider-reported barriers. Funding Sources: This work was supported by the US Department of Agriculture National Institute of Food and Agriculture and the Nebraska Agricultural Experiment Station.